PERENCANAAN KEUANGAN PRIBADI BAGI PENYANDANG DISABILITAS DI BALAI REHABILITASI TERPADU PENYANDANG DISABILITAS DAERAH ISTIMEWA YOGYAKARTA - Suryandari, Ilsa Haruti; Anggraini, Francisca Reni Retno; Hartanto, Hansiadi Yuli (Universitas Sanata Dharma, 2023)
This community service activity aims to provide financial planning training at the Yogyakarta Special Region of Yogyakarta Special Region for the Integrated Rehabilitation of Persons with Disabilities (BRTPD DIY). Based on initial observations, it is known that persons with disabilities have not received training regarding financial management skills. The problem that occurs is that BRTPD DIY has limitations in competent human resources in the field of financial management. The implementation of the activity begins with collecting references on disability. The second stage is to identify the special needs of persons with disabilities. The third stage is the preparation of personal financial planning training materials. The last stage is the implementation of training activities. The results achieved in this community service activity are an increase in the competence of instructors at BRTPD DIY related to financial management. This is to prepare for further activities to include financial management as part of the rehabilitation program in BRTPD DIY.